Longitudinal analysis of ovarian cancer death patterns during a rapid transition period (2005-2020) in Shanghai, China: A population-based study - Li, Xiaopan; Zhang, Mo; Chen, Yichen; Lv, Huihui; Du, Yan (Frontiers in Oncology, 2022)
Objectives: It is important to assess the burden of ovarian cancer related premature death so as to develop appropriate evidence-based care and improve women’s health. This study aimed to characterize the long-term trends in mortality, survival and disease burden of ovarian cancer in Shanghai, China. Materials and Methods: Co-morbidities, crude mortality rate (CMR), age-standardised mortality rate by Segi’s world standard population (ASMRW), years of life lost (YLL), and survival rates were analysed. Temporal trends for the mortality rates and disease burden were analyzed using the Joinpoint Regression Program. Mortality rate increases by demographic and non-demographic factors were estimated by the decomposition method. Results: A total of 1088 ovarian cancer as underlying cause of deaths were recorded. CMR and ASMRW were 4.82/105 and 2.32/105 person-years, respectively. The YLL was 16372.96 years, and the YLL rate was 72.46/105 person-years. The YLL rate increased only in the age group of 70-79 years (P=0.017). The survival rates of ovarian cancer patients did not improve during the ten year period (2005-2015). The top co-morbidities were diseases of the respiratory system, digestive system, and circulatory system. The rates of ovarian cancer deaths caused by non-demographic and demographic factors increased by 21.29% (95%CI: 4.01% to 41.44%, P=0.018) and 25.23% (95%CI: 14.64% to 36.81%, P < 0.001), respectively. Conclusions: Population ageing and all cause of death may affect ovarian cancer related deaths in Pudong, Shanghai. The high mortality and the stagnant survival rates suggest the need for more efforts in targeted prevention and treatment of this disease.